Diaphragmatic Movement at Rest and After Exertion: A Non-Invasive and Easy to Obtain Prognostic Marker in COPD - Mekov E (International Journal of COPD, 2022)
Evgeni Mekov,1 Nikolay Yanev,2 Nedelina Kurtelova,2 Teodora Mihalova,2 Adelina Tsakova,3 Yordanka Yamakova,4 Marc Miravitlles,5 Rosen Petkov2 1Department of Occupational Diseases, Medical University Sofia, Sofia, Bulgaria; 2Department of Pulmonary Diseases, Medical University Sofia, Sofia, Bulgaria; 3Central Clinical Laboratory, Medical University Sofia, Sofia, Bulgaria; 4Department of Anesthesiology and Intensive Care, Medical University Sofia, Sofia, Bulgaria; 5Pneumology Department, Hospital Universitari Vall d´Hebron/Vall d’Hebron Institut de Recerca (VHIR), Vall d’Hebron Hospital Campus; CIBER de Enfermedades Respiratorias (CIBERES), Barcelona, SpainCorrespondence: Marc Miravitlles, Pneumology Department, Hospital Universitari Vall d´Hebron, Pg. Vall d’Hebron 119-129, Barcelona, 08035, Spain, Email marcm@separ.esIntroduction: Diaphragmatic dysfunction is common in patients with chronic obstructive pulmonary disease (COPD). This study aimed to assess the prognostic significance of impaired diaphragmatic movement at rest and after exercise.Methods: This was a prospective study of patients with stable COPD. Diaphragmatic movements were examined at rest and after a 6-minute walking test (6MWT) with a convex transducer with a frequency of 3.5-5-7.5 MHz. Maximal movement of the diaphragm was measured in both right and left diaphragm, and the side with higher amplitude was selected for further analysis. Measurements obtained were evaluated for their prognostic value for a composite endpoint of moderate and severe COPD exacerbations and death in 1 year time period was assessed. In addition, postbronchodilator spirometry, symptoms, quality of life, and demographic and clinical information were collected.Results: A total of 96 patients were analyzed (62.5% male, mean age 65.1 years (standard deviation (SD): 8.1), mean FEV1 (% predicted): 55.8%, SD: 18.3%, mean CAT: 15.6 units, SD: 9.2). Sixty-four patients (67%) presented the composite endpoint. In the multivariate Cox analysis, FVC (HR = 0.944, p = 0.005), CAT score (HR = 1.133, p = 0.011), previous severe exacerbations (HR = 5.446, p = 0.004) and diaphragmatic movement at rest (HR = 0.932, p = 0.033) were found to be predictors of the composite endpoint. This model correctly classified 86.5% (83/96) of the patients.Conclusion: Non-invasive assessment of diaphragmatic movement by ultrasound measurement both at rest and after exercise could contribute to the assessment of disease severity and prognosis of COPD.Keywords: COPD, diaphragmatic dysfunction, comorbidities, thoracic ultrasound, exacerbations